2021
DOI: 10.1111/andr.13135
|View full text |Cite
|
Sign up to set email alerts
|

The upregulation of tryptophan hydroxylase‐2 expression is important for premature ejaculation treatment with the selective serotonin reuptake inhibitor

Abstract: Background: Although there was some evidence to suggest that the serotonergic system in the brain played an important role in premature ejaculation (PE), tryptophan hydroxylase-2 (TPH2) is considered to be the key enzyme for the synthesis of 5hydroxytryptamine (5-HT) and few studies have reported that brain TPH2 is involved in the regulation of ejaculation.Objectives: This study aimed to investigate whether changes in brain TPH2 levels were associated with PE and to explore the effects of acute administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…At present, SSRI has become the first choice for the treatment of PE, and dapoxetine hydrochloride is the first drug specially used for the treatment of PE in the world. Its efficacy and safety in the treatment of PE have been confirmed by many large international multicenter randomized controlled studies 50 . Particularly, Kim et al 51 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…At present, SSRI has become the first choice for the treatment of PE, and dapoxetine hydrochloride is the first drug specially used for the treatment of PE in the world. Its efficacy and safety in the treatment of PE have been confirmed by many large international multicenter randomized controlled studies 50 . Particularly, Kim et al 51 .…”
Section: Discussionmentioning
confidence: 89%
“…Its efficacy and safety in the treatment of PE have been confirmed by many large international multicenter randomized controlled studies. 50 Particularly, Kim et al 51 found that apart from their short-term blocking effect on 5-HT uptake, SSRIs have long-term effects on 5-HT neurotransmission by promoting its synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the research of 5-hydroxytryptamine (5-HT) and its related regulatory genes has a very sufficient theoretical basis [ 14 ]. 5-HT is the most important neurotransmitter and has been found to regulate ejaculation [ 15 ]. Tryptophan hydroxylase (TPH) is an important enzyme for 5-HT synthesis, and its expression level directly influences the synthesis amount of 5-HT, which in turn affects the function of 5-HT [ 16 ].…”
Section: Introductionmentioning
confidence: 99%